PROBLEMS OF MATHEMATICAL EDUCATION OF PRIMARY SCHOOL TEACHERS: IDENTIFYING RELATIONSHIPS BETWEEN CONCEPTS - Sheremeteva, Olga; Turkina, Valentina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The purpose of this article is to investigate how the undergraduate students in the primary education programs understand mathematical information (concepts). Having an understanding of the mathematical content allows the teacher to design different approaches to teaching younger students with different learning styles and abilities. The analysis of theoretical studies published in Russian scientific literature has shown that one of the important criteria for understanding information in a particular field of knowledge is to identify logical connections between the concepts of this field. In this article the authors present the results of their study on how undergraduate students studying in the profiles of “Primary Education" and "Psychological and Pedagogical Education” form the links between the concepts used in everyday life versus the connections between mathematical concepts. The results show that other disciplines/ fields of study influence the formation of connections between mathematical concepts. In addition, some specific difficulties in establishing some of these connections were identified. Based on this research, the authors provide recommendations on specific strategies to improve the professional education for future teachers in the area of mathematical knowledge.